2015
DOI: 10.1364/ao.54.007082
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dual-polarization LTE radio over a free-space optical turbulence channel

Abstract: A dual polarization (DP) radio over a free-space optical (FSO) communication link using a long-term evolution (LTE) radio signal is proposed and analyzed under different turbulence channel conditions. Radio signal transmission over the DP FSO channel is experimentally verified by means of error vector magnitude (EVM) statistics. We demonstrate that such a system, employing a 64 quadrature amplitude modulation at the frequency bands of 800 MHz and 2.6 GHz, evinces reliability with <8% of EVM in a turbulent chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The atmospheric chamber set up for measurements in the facilities of the Czech Technical University in Prague [27] features two heater fans, and one Glycerine machine, that can blow hot air and fog into the chamber, respectively. For the characterization of turbulence and light scintillation in the chamber, an array of 20 temperature sensors were set up equidistantly.…”
Section: Laboratory Chambermentioning
confidence: 99%
See 1 more Smart Citation
“…The atmospheric chamber set up for measurements in the facilities of the Czech Technical University in Prague [27] features two heater fans, and one Glycerine machine, that can blow hot air and fog into the chamber, respectively. For the characterization of turbulence and light scintillation in the chamber, an array of 20 temperature sensors were set up equidistantly.…”
Section: Laboratory Chambermentioning
confidence: 99%
“…The experiments carried out for this work were done using a laboratory chamber, and the conditions emulated were of heat-induced turbulence and the presence of fog in the air. The refractive index structure parameter (C 2 n ) [27] is used to estimate the level of turbulence and the meteorological visibility (V M ) as a measure of the level of fog. The fog experiments are especially relevant because we utilize the camera's built-in amplifier to overcome the fog attenuation and mitigate the relative contribution of the quantization noise induced by the analog-to-digital conversion stage, ensuring an improvement of the signal quality without increasing the exposure time, and, thus, keeping a high bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…To measure the temperature profile and determine the temperature gradient along the channel, we placed 20 thermal sensors at an interval of 10 cm along the FSO channel. We used Rytov variance and the refractive index structure parameter to characterize strength of the turbulence according to [22]. The variance of the log-intensity signal fluctuation defined by Rytov variance R 2 is given by [31]:…”
Section: Fso Turbulence Effectsmentioning
confidence: 99%
“…The authors reported a predicted power penalty of ~25 dB at a symbol error probability of 10E-8 for the strong turbulence regime (Rytov variance σR 2 of 3.5). The first concept of the dual-polarization multiplexing RoFSO system proposed for the LTE radio signal was investigated in [22].…”
Section: Introductionmentioning
confidence: 99%
“…In outstretching technology of optical communication system, several systems use the radio-over-fiber (ROF) technology. The main purpose of this method is integration with other networks and low dispersion [4][5]. But, integration the radio frequency (RF) wave with FSO system is hardly affected by the atmosphere turbulent that is one of the advantage of radio over free space communication [6].…”
Section: Introductionmentioning
confidence: 99%